Evaluation of Dietary Supplement Use in Wheelchair Rugby Athletes - Madden, Robyn F. (Nutrients, 2018)
Wheelchair rugby is a rapidly growing Paralympic sport; however, research remains predominantly in the realms of physiology and biomechanics. Currently, there is little investigation into nutrition and dietary supplement use among wheelchair rugby athletes (WRA). The aim of this study was to assess the types of dietary supplements (DS) used, the prevalence of usage, and the reasons for use among WRA. The secondary aim was to report utilized and preferred sources of nutritional information among this population. A valid, reliable Dietary Supplement Questionnaire was used to report supplement use and reasons for use. Male (n = 33) and female (n = 9) WRA were recruited at a national tournament and through emailing coaches of various Canadian teams. Dietary supplement usage was prevalent as 90.9% of males and 77.8% of females reported usage within the past three months with the most regularly used supplements being vitamin D (26.2%), electrolytes (19.5%), and protein powder (19.5%). The most common reason for usage was performance. The top sources of nutrition information were dietitian/nutritionist and the internet. Further investigation into DS use is needed to help create nutritional guidelines that are accessible to WRA and athletes with disabilities in general.